MICROFIELD OF GRAY COLOR IN INTERIOR ADVERTISING - Sovyetna, Alyona; Sovyetnyi, Eduard (SWorld-Ger Conference proceedings, 2022)
In our work, advertising texts in three languages ​​were analyzed, in particular gray color in interior advertisements. Achromatic color markings are less commonly used, but one can notice a tendency to activate light tones - microfields of white and gray